BRAND JOURNALISM ACT DALAM MEMBANGUN BRAND PERSONALITY SEBAGAI NGO PROFESSIONAL - Diah Pitaloka Margareta; Suharjo Nugroho (Virtu: Jurnal Kajian Komunikasi, Budaya dan Islam, 2022)
This research departs from a critical analysis about the relevance of the Edelman Trust survey with NGOs in Indonesia and the importance of brand journalism for Public Relations in achieving the goals and tasks of NGO Public Relations. This study aims to determine the implementation of the Aksi Cepat Tanggap (ACT) brand journalism in building a brand personality as a professional NGO.  This research uses the concept of three key activities of brand journalism; Every Company is Media Company, the key of storytelling, and the concept of soft-selling Public Relations in the context of brand journalism. This study uses a constructivist paradigm and a qualitative approach with interviews also document data collection methods. The informants in this study were ACT employees who provided relevant information under the characteristics based on specific considerations, using the purposive sampling technique. We collect document data from the ACT media platform and mass media coverage by the informant's statement. Based on the research, the conclusion is that ACT's brand journalism used to build ACT's brand personality as an NGO Professional is to determine audience segmentation. They use the soft-selling process of Public Relations in creating storytelling, differentiating storytelling that contains values of volunteerism, generosity, and humanity, emphasizing emotional and human interest based on facts, and conveying storytelling through various publication platforms owned by ACT.